Overrepresentation of English Learners in Special Education Amid the COVID-19 Pandemic. Issue 2 (3rd April 2021) - Ortogero, Shawna P.; Ray, Amber B.
ABSTRACT: The continued concern of English Learners (ELs) being overrepresented in special education coupled with the 2020 global COVID-19 pandemic that urged educators to ramp up online instruction, has left educators to deliver instruction to ELs via e-learning. This issue is further exacerbated by students in the United States (U.S.) continuing to lag behind their peers in other countries in foreign language capabilities. The U.S. can gain valuable insights from other countries when it comes to boosting the vocabulary acquisition skills of ELs, as learning new vocabulary is key for ELs to develop English proficiency. This review of eight international studies indicated the following effective vocabulary acquisition strategies (VAS) feasible for instructing English learners via e-learning: (1) using the native language to teach English; (2) Content Language Integrated Learning; (3) designing culturally relevant activities in both the first and second language; (4) pre teaching vocabulary multimodally using explicit word learning strategies; (5) use of multimedia; and (6) promoting self-regulation. A Self-Regulated Multimedia Cognitive Learning Model for educators to implement VAS with ELs amid a time of enhanced virtual learning is also introduced.